Global politics - Murphy, Robert; Jefferies, John; Gadsby, Josie (Hodder Education, 2022)
- Newly revised to accompany the Pearson Edexcel specification for Global Politics, with updated case studies and recent developments from around the world - Provides synoptic links within global politics, and across UK and political ideas topics - Includes definitions of key terms and concepts throughout - Includes quickfire knowledge-check questions and summaries of key content to help consolidate knowledge and understanding - Features practice questions throughout, helping students improve their analysis and evaluation skills - Provides answer guidance for exam-style questions online on the Hodder Education website.